Folds inside pebbles: When do they form during conglomerate deformation? Numerical modelling and comparison with the Hutuo Group conglomerates, North China Craton. (July 2022) - Ran, Hao; Bons, Paul D.; Wang, Genhou; Griera, Albert; de Riese, Tamara; Gomez-Rivas, Enrique; Llorens, Maria-Gema; Ran, Shuming; Wang, Yao; Wang, Shubiao
Abstract: The analysis of folds within pebbles in conglomerates has been used to infer deformation events before deposition of the conglomerate. However, it is not clear whether folds can develop within pebbles during subsequent conglomerate deformation. We use numerical modelling to investigate folding within internally layered pebbles in a ductile deformation regime and simple shear deformation. We vary the initial orientation and rheology of the layers within pebbles, as well as the relative rheology of the conglomerate matrix, for single isolated pebbles and multiple interacting pebbles. We use a power-law viscous rheology for both the pebbles and their matrix. Folding within pebbles can indeed occur, but only within a narrow range of initial layer orientations, strength or viscosity ratio between the internal layers and that of the matrix relative to the pebble layers. Results are used to interpret the strongly deformed conglomerates from the Proterozoic Hutuo Group in the Wutai Mountains, North China Craton, that contain a small percentage of pebbles with internal folds. Based on field observations and numerical modelling results, we suggest that these formed during deformation of the conglomerate and do not represent inclusion of previously folded lithologies into the unit. Highlights: The development of folds within layered pebbles of conglomerates is simulated in simple shear with ELLE + VPFFT code. Initial orientation and rheology of layers within pebbles control the formation of internal folds. Folding within pebbles can indeed occur, but only within a narrow range of initial layer orientations and rheology. Folds within the BIF pebbles of conglomerates at the base of the Hutuo Group formed after the conglomerate deposition.